PERBANDINGAN EFISIENSI DYE SENSITISIZED SOLAR CELL (DSSC) DARI EKSTRAK DAUN PACAR AIR, EKSTRAK BUNGA PACAR AIR MERAH DAN UNGU (IMPATIENS BALSAMINA LINN) SEBAGAI DYE SENSITIZER - Alimuddin, Arni; Iswadi, Iswadi; Sahara, Sahara (Universitas Islam Negeri Alauddin Makassar, 2016)
Research on Comparison Of Efficiency Dye Sensitized Solar Cell (Dssc) Of Henna Leaf Extract Water, Water Henna Flower Red And Purple (Impatiens Balsamina Linn) as a Dye Sensitizer in order to determine how much comparative efficiency of dye sensitisized solar cell (DSSC ) of water henna leaf extract, flower extract water henna red and purple as a dye sensitizer. The method used in this research is the method of Doctor Blade. Based on the results of measurements of I-V by using a source of light, the efficiency gained from henna leaf extract 0.008473333% water by absorption spectrum wavelengths are in the range of 245- 660.50 nm and an absorbance of 0.036. For efficient water henna red flowers of 0.007466667% of this extract is the wavelength range of 242.50 - 312 500 nm and absorbance of 4573, while for the water purple flowers girlfriend 0.004833333% efficiency results obtained in the wavelength range 238.50 - 350.50 nm and absorbance 4,617 , Henna leaf extract water as a dye sensitizer on sensitisized dye solar cell (DSSC) have the highest efficiency.